2010
DOI: 10.1002/adsc.200900869
|View full text |Cite
|
Sign up to set email alerts
|

Pentafluorophenylammonium Trifluoromethanesulfonimide: Mild, Powerful, and Robust Catalyst for Mukaiyama Aldol and Mannich Reactions between Ketene Silyl Acetals and Ketones or Oxime Ethers

Abstract: Pentafluorophenylammonium trifluoromethanesulfonimide (C 6 F 5 N + H 3 ·NTf 2 À ) promotes Mukaiyama aldol and Mannich reactions using ketene silyl acetals with ketones and oxime ethers, respectively. The present robust method is mild, but powerful enough to utilize less accessible electrophiles such as enolizable ketones and oxime ethers to produce a variety of b-hydroxy esters and b-alk-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In this review, we have showed that much excellent progress has been made in the development of the homogeneous catalytic aldol reaction, which offer many valuable synthetic tools to construct new carbon-carbon bond and make complex or chiral carbonyl compounds directly. It is no problem that the invention of a novel type of homogeneous catalysts in the aldol reaction is a competitive and attractive research field (320)(321)(322)(323)(324)(325). Moreover, the studies with versatile substrates inspired from simple aldehydes or ketones have shown that aldol reaction is a powerful process to prepare desired molecules (326)(327)(328)(329)(330)(331).…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we have showed that much excellent progress has been made in the development of the homogeneous catalytic aldol reaction, which offer many valuable synthetic tools to construct new carbon-carbon bond and make complex or chiral carbonyl compounds directly. It is no problem that the invention of a novel type of homogeneous catalysts in the aldol reaction is a competitive and attractive research field (320)(321)(322)(323)(324)(325). Moreover, the studies with versatile substrates inspired from simple aldehydes or ketones have shown that aldol reaction is a powerful process to prepare desired molecules (326)(327)(328)(329)(330)(331).…”
Section: Discussionmentioning
confidence: 99%
“…PFPAT as an efficient organo-catalyst was applied in various transformations. From the literatures, it was found that PFPAT is a useful catalyst for multi-component reactions (MCRs) [16–22] , since it is low toxic catalyst, air and water compatible and has remarkable ability to suppress side reactions in acid-sensitive substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Funatomi et al reported the application of pentafluorophenylammonium triflate (C 6 F 5 NH 3 OTf; PFPAT) as a novel heterogeneous catalyst in organic transformation such as esterification of carboxylic acids with alcohols [16] , C-acylations of enol silyl ethers or ketene silyl (thio)acetals with acid chlorides [17] and Mukaiyama aldol and Mannich reactions using ketene silyl acetals with ketones and oxime ethers [18] . Further, PFPAT also used as the catalyst for acylation of alcohols, phenols, and amines [19] , one-pot condensation of β-naphthol, aldehydes and cyclic 1,3-dicarbonyl compounds [20] , synthesis of xanthenes derivatives [21] , and Biginelli reaction [22] .…”
Section: Introductionmentioning
confidence: 99%
“…[45][46][47][48] Organocatalysts have received extensive recognitions in organic synthesis due to its unique properties of being readily affordable, selectivity, longer catalyst life, negligible equipment corrosion, ease of product separation, nontoxic and reusability. Of these, pentafluorophenylammonium triflate (PFPAT) has emerged as a powerful Brønsted acid catalyst to perform many useful organic transformations [49][50][51][52][53][54][55][56][57] under mild reaction conditions. Due to the current challenges for developing environmentally benign synthetic processes and in continuation of our interest in the application of new organocatalysts for various organic transformations, [52][53][54][55][56][57] we report an efficient route for the synthesis of α-aminophosphonate derivatives using PFPAT as a catalyst (scheme 1).…”
Section: Introductionmentioning
confidence: 99%